Effects of the inclusion of personal development contents in a parenting program for at-risk families - Peña, Margarita; Máiquez, María L.; Rodrigo, María J. (Anales de Psicología / Annals of Psychology, 2013)
This study analyses the results of the Personal and Familiar Support Program, targeted to families referred by the Social Services of the Island of Palma, Canary Islands, with regard to its immediate effects obtained on the parental agency and the educational practices of the participants. The results showed that the incorporation of personal development contents together with those of educational skills allowed for improving the results obtained in previous trials in which only contents of educational skills were included. Likewise, as a novelty with respect to previous evaluations, it was obtained that the above results were not modulated by the level of risk. Finally, in addition to the variable-centered approach, a person-centered approach was adopted to analyze the different pattern of change found among the participants in the dimensions previously studied, and the variables that characterize every typology of change. The discussion emphasizes the relevance of including personal development contents in the parent education with at-risk families.